Can superabsorbent polymers be used as rheology modifiers for cementitious materials in the context of 3D concrete printing?. (31st March 2023) - Chen, Yu; Liang, Minfei; Zhang, Yu; Li, Zhenming; Šavija, Branko; Schlangen, Erik; Çopuroğlu, Oğuzhan
Highlights: Adding SAP increased dynamic yield stress and apparent viscosity of LC3 pastes. Structural build-up and hydration of LC3 pastes were enhanced by the use of SAP. Using SAP effectively mitigated the autogenous shrinkage of LC3 pastes for up to 7 days. Compressive strength at 3, 7 and 28 days was decreased by increasing SAP dosage. SAP could act as a promising rheology modifier for 3D concrete printing. Abstract: Autogenous shrinkage may be a critical issue concerning the use of limestone-calcined clay-cement (LC3) in high-performance concrete and 3D printable cementitious materials, which have relatively low water to binder (W/B) ratio. Adding an internal curing agent, i.e., superabsorbent polymer (SAP), could be a viable solution in this context. However, employing SAP (without adding additional water) may also influence the fresh properties of LC3 composites by increasing yield stress and viscosity, which may be beneficial for 3D printability. Therefore, this study attempts to use SAP as a rheology modifying admixture with the aim of investigating the impact of SAP on flow behavior, structural build-up, hydration kinetics, compressive strength, and autogenous shrinkage of LC3 pastes with a fixed W/B (0.3). In addition, hydroxypropyl methylcellulose (a typical rheology/viscosity modifier in 3D printable cementitious materials) was also employed in two mixtures to compare their effects. Results show that adding SAP increases the dynamic yield stress and the apparent viscosity, as well as structural build-up and hydration, but decreases the compressive strength at 3, 7 and 28 days. Furthermore, using SAP (especially 0.2 wt% SAP) not only promotes the early-age expansion but also effectively mitigates the autogenous shrinkage of LC3 pastes for up to 7 days. Overall, the obtained results indicated that SAP could act as a promising rheology modifier for the development of 3D printable cementitious materials.